2015
DOI: 10.1007/s00240-015-0772-6
|View full text |Cite
|
Sign up to set email alerts
|

The application of S.T.O.N.E. nephrolithometry in pediatric patients with upper urinary tract calculi treated with mini-percutaneous nephrolithotomy

Abstract: The purpose of this study is to verify the applicability of S.T.O.N.E. nephrolithometry in pediatric patients. 103 cases of pediatric patients younger than 4 years old with upper urinary tract calculi treated with mini-percutaneous nephrolithotomy from January 2012 to March 2014 were retrospectively reviewed and evaluated using this scoring system. All procedures were performed under general anesthesia, using a 14-French nephroscope through a 16-French working access. All patients were divided into two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Of the patients, 58.3% were male and 41.7% were female. The mean BMI value was 27.2 (23)(24)(25)(26)(27)(28)(29)(30)(31) kg/m 2 . There was hypertension in 35% of the patients and diabetes mellitus in 25%.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Of the patients, 58.3% were male and 41.7% were female. The mean BMI value was 27.2 (23)(24)(25)(26)(27)(28)(29)(30)(31) kg/m 2 . There was hypertension in 35% of the patients and diabetes mellitus in 25%.…”
Section: Resultsmentioning
confidence: 98%
“…Okhunov et al 8 found estimated blood loss, length of hospital stay, and operation time to be significant. Doulian et al 29 applied S.T.O.N.E. nephrolithometry score to the pediatric age group and found that the estimated blood loss and length of hospital stay were insignificant.…”
Section: Stone Nephrolithometry and Pcnlmentioning
confidence: 99%
“…Pediatric patients have a small renal reserve and quietly feeble renal parenchyma, therefore pediatric PCNL can be a life threatening procedure. Mini-PCNL using 14 French to 16 French working tract, is effective and safe for pediatric renal stones management 22 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is a relative lack of studies evaluating these scoring systems in pediatrics. 16 in children with upper urinary tract stones managed by mini-PCNL. The authors concluded that (S.T.O.N.E.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation